Can transformational leadership influence on teachers’ commitment towards organization, teaching profession, and students learning? A quantitative analysis - Ibrahim, Mohammed Sani; Ghavifekr, Simin; Ling, Sii; Siraj, Saedah; Azeez, Mohd Ibrahim K. (Asia Pacific education review, 2014)
This study investigates the impact of transformational leadership as idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration on teachers’ commitment towards organization, teaching profession, and students’ learning. A quantitative survey method was applied, and four broadly hypothesized relationships were tested with a sample of 1,014 trained non-graduate and graduate teachers serving in twenty-seven secondary schools in Sarawak, Malaysia. The results indicate a moderate level of teachers’ commitment and a low level of transformational leadership qualities among the respondents. This study found that inspirational motivation, individualized consideration, and intellectual stimulation were the factors contributing towards teachers’ commitment to teaching profession, and there was no dominant factor influencing commitment to students’ learning. Moreover, it was discovered that inspirational motivation was a factor to teachers’ efficacy and teaching experience. Besides, teachers’ efficacy and teaching experience were predictors to teachers’ commitment to organization, teaching profession, and students’ learning, respectively. These findings revealed that there was a significant relationship between transformational leadership and teachers’ commitment to organization and teaching profession, but not students’ learning. The results of this study indicate the necessity for leadership development of school leaders so that they could systematically acquire and internalize the effective transformational leadership qualities that are crucial in changing teachers’ attitude and improving their commitment towards their profession.